2019
DOI: 10.1039/c9cp00398c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insight into carboxylic acid–alkali metal cations interactions: reversed affinities and ion-pair formation revealed by non-linear optics and simulations

Abstract: Alkali metal cations’ relative affinity to the carboxylic acid moiety is pH dependent, and typically remain hydrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
125
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(144 citation statements)
references
References 83 publications
16
125
0
3
Order By: Relevance
“…The negative charge and accompanying surface potential result in surface proton concentrations that are several orders of magnitude higher than in the bulk. Moreover, the charging behavior upon addition of monovalent ion salts to solution has been shown to be consistent with the Gouy-Chapman theory for concentrations ≤50 mM 26,27 .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The negative charge and accompanying surface potential result in surface proton concentrations that are several orders of magnitude higher than in the bulk. Moreover, the charging behavior upon addition of monovalent ion salts to solution has been shown to be consistent with the Gouy-Chapman theory for concentrations ≤50 mM 26,27 .…”
Section: Resultssupporting
confidence: 61%
“…The different polarizations provide complementary information about the surface species and their orientation. The assignements are taken from refs [26][27][28][29]. and this study (see text).…”
mentioning
confidence: 99%
“…26 Previous VSFS studies using arachidic acid, a fatty acid with a twenty carbon alkyl chain, have shown that the charging behavior of the monolayer at pH 6 is in excellent agreement with the Gouy Chapman model predictions for ionic strengths ≤ 50 mM, 23 but deviates at salt concentrations ≥ 100 mM. 24 For the high salt concentrations, the data was instead consistent with the steric MPB model using an effective ion size of ~7.5 Å for Na + . 24 In those studies,…”
mentioning
confidence: 72%
“…24 For the high salt concentrations, the data was instead consistent with the steric MPB model using an effective ion size of ~7.5 Å for Na + . 24 In those studies,…”
mentioning
confidence: 74%
“…Furthermore, most carbohydrate polymers have a positive chi‐parameter which means that their interaction with water is typically not stronger than interactions between water molecules . However, the added carboxyl groups on the surface of CNFs are strongly hydrated, but at a charge density of 0.6 mmol g −1 , the coverage is moderate and at low pH, most of the carboxyl groups are protonated and the chaotropic properties dominate …”
Section: Resultsmentioning
confidence: 99%